Análise de gênero das seções de resultados e de discussão de artigos acadêmicos experimentais da agronomia - Otaran, Maíra da Silva (2018)
The reading and production of academic articles (AA) in English is an important social and discursive practice in the academic sphere for the exchange of new discoveries in different areas of knowledge, among them Agronomy. Specifically at the Federal University of Santa Maria (UFSM), there is a growing demand for scientific literacy in this area and in English, especially for the production of academic articles to be published in international journals with a high impact factor. In this context, it becomes necessary to research in Genre Analysis (GA) aimed at teaching writing and reading academic articles for Agronomy. In order to contribute to the fulfillment of this demand, this work aims to analyze the rhetorical organization (SWALES, 1990; 2004) and to describe in detail the lexical-grammatical features characteristic of the Results and Discussion sections of Agronomy research articles. The corpus of analysis consists of thirty Results and Discussion sections collected from two Agronomy representative journals (Agriculture, Ecosystems & Environment and Agronomy Journal), in the period of 2014-2017, and it was analyzed in terms of textual and contextual features. The textual analysis of the Results and Discussion sections showed that the Results section appears separate from the Discussion section and typical linguistic marks of this disciplinary context are the use of passive voice and first person to report results, use of comparatives and logical connectors to the explain the (un)expected results of the reported research and typical agronomic research verbs, such as increase, decrease, range. The contextual analysis of the publications manuals of the journals showed that the norms for the writing of the Results and of Discussion sections together or separated are not explicit and that this decision seems to be of the authors of the reported research. With the systematization of the rhetorical organization and the typical linguistic marks of the Results and Discussion sections, it is possible to develop academic writing courses geared to this disciplinary context and that suppose the demand for the production of research articles in this area.